Gender Inequality and Workplace Health: Assessing Discrimination among Female State Government Officials - Nor Hanim, Awang @ Mohd Noor; Leha, Saliman; Nurhidayah, Marzuki; Norfatiha, Othman (Journal of Chemical Health Risks (JCHR), 2024)
The problem of discrimination against women in the workplace is still an ongoing issue in Malaysia. The opportunity for women to make a paradigm shift in developing their careers in terms of decision making, career development opportunities and promotion may therefore encounter various problems. It is interesting to find out whether discrimination against female employees also occurs in the state government offices in the district of Kota Bharu, Kelantan. The aim of this study is to analyze the extent of discrimination against female government employees in the workplace in Kelantan, Malaysia. The research utilized quantitative design methods based on descriptive analysis through structured and unstructured interviews and observations conducted in this study with 262 respondents in the state of Kelantan. Data obtained from the structured interviews were analyzed descriptively and using multiple regression analysis, while observations were analyzed by incorporating field notes and visual images. The results show that the extent of discrimination against female civil servants is at a medium level. Four factors influence discrimination against female civil servants in this study, namely situational factors, socialization factors, attitudes and income level. This study suggests that the low level of education of government officials working in Kota Bharu district makes them (employees) more likely to discriminate against female employees.